Identification of a population of X-ray-emitting massive stars in the Galactic plane - Anderson, Gemma; Gaensler, B.; Kaplan, D.; Posselt, B.; Slane, P.; Murray, S.; Mauerhan, J.; Benjamin, R.; Brogan, C.; Chakrabarty, D.; Drake, J.; Drew, J.; et al. (Institute of Physics Publishing, 2011)
We present X-ray, infrared, optical, and radio observations of four previously unidentified Galactic plane X-ray sources: AX J163252-4746, AX J184738-0156, AX J144701-5919, and AX J144547-5931. Detection of each source with the Chandra X-ray Observatory has provided sub-arcsecond localizations, which we use to identify bright infrared counterparts to all four objects. Infrared and optical spectroscopy of these counterparts demonstrate that all four X-ray sources are extremely massive stars, with spectral classifications: Ofpe/WN9 (AX J163252-4746), WN7 (AX J184738-0156 = WR121a), WN7-8h (AX J144701-5919), and OIf+ (AX J144547-5931). AX J163252-4746 and AX J184738-0156 are both luminous, hard, X-ray emitters with strong Fe xxv emission lines in their X-ray spectra at ~6.7 keV. The multi-wavelength properties of AX J163252-4746 and AX J184738-0156 are not consistent with isolated massive stars or accretion onto a compact companion; we conclude that their X-ray emission is most likely generated in a colliding-wind binary (CWB) system. For both AX J144701-5919 and AX J144547-5931, the X-ray emission is an order of magnitude less luminous and with a softer spectrum. These properties are consistent with a CWB interpretation for these two sources also, but other mechanisms for the generation of X-rays cannot be excluded. There are many other as yet unidentified X-ray sources in the Galactic plane, with X-ray properties similar to those seen for AX J163252-4746, AX J184738-0156, AX J144701-5919, and AX J144547-5931. This may indicate a substantial population of X-ray-emitting massive stars and CWBs in the Milky Way. © 2011. The American Astronomical Society.